일부 치위생과 학생의 아르바이트 경험이 대학생활적응에 미치는 영향 - 신선행; Seon Haeng Shin (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The purpose of the study is to find out the effect of part-time employment experience on adaptation to university life in dental hygiene students. Methods: A self-reported questionnaire was completed by 288 dental hygiene students in Seoul and Gyeonggido from September to October, 2014. The questionnaire consisted of general characteristics of the subjects(5 items), part-time employment experience(6 items), and adaptation to university life(53 items). The instrument for adaptation to university life was adapted from Baker and Sirky and modified by Kwon. Likert 5 point scale adaptation included personal emotion adaptation, academic adaptation, social adaptation, and university environment adaptation. Cronbach’s α was 0.80 in the study. Results: The adaptation to university life was 3.0 points. The higher the economic level was, the higher the personal emotional adaptation(p<0.001) and academic adaptation were(p<0.05). The adaptation to university life was positively influenced by tuition support by parents and part-time employment(p<0.05). The part-time employment was significantly helpful to future job selection, social adaptation, and university environment adaptation(p<0.001). Economic stability and advantage of future job selection had a positive influence on the adaptation to university life. So the adaptation to university life was proportional to younger age, economic stability, and advantage to future job selection. Conclusions: It is very important to give a positive motivation and stimulation, and a careful counseling to the students in part-time employment. In order to encourage the part-time employed students, major-related part-time job opening must be given.